Therapeutic potential of gastro-gastric fistulas created via lumen-apposing metal stents for nutritional deficiencies after roux-en-y gastric bypass - Kadkhodayan, Kambiz; Hussain, Azhar; Abassi, Abdullah; Chandan, Saurabh; Pathak, Sagar; Bello Vincentelli, Gustavo; Cosgrove, Natalie; Arain, Mustafa A; Hayat, Maham; Jain, Deepanshu; Viana, Artur; Almujarkesh, Mohamad Khaled; Alsaleh, Tareq; Elamin, Magda; Khan, Nihal Ijaz; Yang, Dennis; Irani, Shayan; Hasan, Muhammad Khalid (Endoscopy International Open, 2025)
Roux-en-Y gastric bypass (RYGB) is an effective long-term weight loss operation with improvements in metabolic diseases. Nutritional deficiencies, however, are highly prevalent despite supplementation, largely due to exclusion of the proximal small bowel. In RYGB patients who require pancreaticobiliary access, the EUS-directed transgastric ERCP (EDGE) procedure provides a stable gastro-gastric (GG) fistula using a lumen-apposing metal stent (LAMS). The metabolic and nutritional effects of temporary food diversion remain unknown.We conducted a review of 60 consecutive RYGB patients from two tertiary centers who underwent EDGE. Nutritional and metabolic parameters were assessed before LAMS placement and after removal.Mean age was 63.2 ± 11.05 years; 23% were male. Significant improvements were observed in serum hemoglobin (mean difference (MD) 1.1 g/dL; P = 0.004), vitamin B12 levels (MD 204.4 pg/mL; P = 0.021), iron (MD 57.9 mcg/dL; P = 0.017), albumin (MD 0.4 g/dL; P = 0.013), and magnesium levels (MD 0.24 mg/dL; P = 0.016). In addition, serum folate (MD 2.2 μg/mL; P = 0.873), and ferritin levels (MD 315.5 μg/mL; P = 0.335), showed improvement trends, but these did not reach statistical significance. No significant changes were observed in total body weight, body mass index, serum glucose, hemoglobin A1c, serum triglycerides, low-density lipoprotein, or high-density lipoprotein (P > 0.05 for all).Temporary partial-reversal of RYGB using a LAMS improves key nutritional parameters without compromising metabolic benefits of RYGB. These findings may support a therapeutic role for iatrogenic GG fistulas as a minimally invasive option for RYGB patients with refractory nutritional deficiencies.
Keywords: Endoscopic ultrasonography; Intervention EUS; Endoscopy Lower GI Tract; Stenting